Bacterial community analysis of infant foods obtained from Chinese markets by combining culture-dependent and high-throughput sequence methods. (December 2022) - Yuan, Lei; Fan, Luyao; Liu, Siqi; Sant'Ana, Anderson S.; Zhang, Yanhe; Zhou, Wenyuan; Zheng, Xiangfeng; He, Guoqing; Yang, Zhenquan; Jiao, Xinan
Graphical abstract: Highlights: Fifteen genera and 41 species were identified in infant foods by cultivation. Enriched biodiversity with different bacterial population was found by HTS. High prevalence of pathogens in infant foods was found. Bacillus licheniformis was widespread in infant foods with diverse genotypes. Abstract: In this study, twenty-two baby foods including cereal-based products and powdered infant formula (PIF) obtained from local markets were comprehensively investigated for their bacterial contamination using culture-dependent and high-throughput sequence (HTS) methods. In addition, the genetic diversity and biofilm-forming capacity of the most abundant species were analyzed using random amplified polymorphic DNA (RAPD) and crystal violet staining assay, respectively. Results showed that 170 mesophilic isolates collected from 22 samples were clustered into 15 genera and 41 species. Bacillus (77.65%) was the most prevalent genus, followed by Paenibacillus (7.06%), Alkalibacillus (3.53%), and Lysinibacillus (2.35%). Bacillus licheniformis (49.41%) proved to be the most dominant species in infant foods, and a high genetic diversity with six different RAPD profiles was observed. A total of 87.5% of B. licheniformis isolates were identified as strong biofilm formers, and heterogeneous biofilm-forming ability was observed among the isolates sharing the same RAPD pattern. HTS analysis revealed an 18-fold higher biodiversity at the genus level, and a significantly different bacterial community of infant foods was dominated by Lactococcus, Streptococcus, and Bifidobacterium . Foodborne pathogens including Bacillus cereus, and potentially pathogenic microorganisms such as Acinetobacter baumannii, were identified in infant foods by HTS. The current results could expand the crucial information about bacterial contamination of baby foods.